2010
DOI: 10.1042/bj20101100
|View full text |Cite
|
Sign up to set email alerts
|

Contraction regulates site-specific phosphorylation of TBC1D1 in skeletal muscle

Abstract: TBC1D1 (tre-2/USP6, BUB2, cdc16 domain family member 1) is a Rab-GAP (GTPase-activating protein) that is highly expressed in skeletal muscle, but little is known about TBC1D1 regulation and function. We studied TBC1D1 phosphorylation on three predicted AMPK (AMP-activated protein kinase) phosphorylation sites (Ser231, Ser660 and Ser700) and one predicted Akt phosphorylation site (Thr590) in control mice, AMPKα2 inactive transgenic mice (AMPKα2i TG) and Akt2-knockout mice (Akt2 KO). Muscle contraction significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(129 citation statements)
references
References 45 publications
7
122
0
Order By: Relevance
“…On the other hand, mutation of Ser-237 to alanine has no effect on the APPL2-TBC1D1 interaction as well as on the suppressive effect of TBC1D1 on insulin-stimulated glucose uptake. Of note, Ser-237 is phosphorylated by AMPK in response to contraction but not by insulin stimulation (40)(41)(42), suggesting that APPL2 may only regulate glucose uptake through the TBC1D1 signaling pathway in response to insulin and not contraction in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mutation of Ser-237 to alanine has no effect on the APPL2-TBC1D1 interaction as well as on the suppressive effect of TBC1D1 on insulin-stimulated glucose uptake. Of note, Ser-237 is phosphorylated by AMPK in response to contraction but not by insulin stimulation (40)(41)(42), suggesting that APPL2 may only regulate glucose uptake through the TBC1D1 signaling pathway in response to insulin and not contraction in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with recent studies in healthy lean (24,25) and obese (26) subjects. Mutational studies in mice have shown that lack of phosphorylation on multiple sites on TBC1D1, including Ser 237 and Thr 596 , reduce contraction-stimulated glucose uptake in skeletal muscle (27,45). Furthermore, the TBC1D1 conventional knockout mouse model shows impaired muscle glucose uptake in response to exercise (46).…”
Section: Discussionmentioning
confidence: 99%
“…TBC1D1 is a closely related paralog of TBC1D4 that is regulated by both AMPK and Akt, and regulates glucose transport (37)(38)(39)(40). As AMPK increases the phosphorylation of TBC1D1 Ser 231 in response to contraction and AICAR, and as Akt increases the phosphorylation of Thr 590 in response to insulin, we investigated whether changes in TBC1D1 phosphorylation occurred in parallel with the increase in muscle insulin sensitivity after prior AICAR stimulation.…”
Section: Tbc1d1 Signalingmentioning
confidence: 99%